EFFECTIVENESS OF THE REALISTIC MATHEMATICS EDUCATION APPROACH TO THE ABILITY TO SOLVE MATHEMATICAL PROBLEMS - Mamik Suendarti; Hawa Liberna (Universitas Sembilanbelas November Kolaka, 2019)
The purpose of this study is to find out how effective the Realistic Mathematics Education (RME) approach is. The research method used in this study is the experimental method. The sampling technique uses simple random sampling technique. The instrument for collecting data in this study is an essay test consisting of 8 items. The data analysis technique used is the t-test, and based on the t-test calculation shows t-count = 10,098 and t-table = 2,002 at the significant level of 5% or (???? = 0,05) and the degree of freedom (dk = 58) which means t-count t table (10,098 2,002) then H0 is rejected and H1 is accepted. The conclusion is that the average mathematical problem solving ability of students given the Realistic Mathematics Education (RME) approach is higher than the mathematical problem solving abilities of students who are given an expository approach. And the effectiveness calculation for the Realistic Mathematics Education (RME) approach is quite high, which is 2,605. Thus, there is an influence and effectiveness of the Realistic Mathematics Education (RME) approach in the teaching and learning process.